Time-Varying Risk Aversion: A Dynamic Application in Index Hedging - Phringphred, Aran (Thammasat Review of Economic and Social Policy, 2019)
Degree of risk aversion has recently been claimed as important factor in determining hedge ratio level since the conventional minimum variance hedge ratio (MVHR) with risk minimization objective can lead to a suboptimal hedge level. By taking into account investors’ risk attitude through their degree of risk aversion and expected return, the risk aversion hedge ratio (RAHR) can help investors maximise their utility. A GARCH-M model was estimated to determine time varying risk aversion (TVRA) and classify short and long hedgers. Multivariate GARCH-DCC model was then applied, to estimate the expected return equation model and conditional variance and covariance models, and to determine the optimal hedge ratio of RAHR. The results revealed that the RAHR portfolio with lower hedge ratio outperformed MVHR portfolio for both short and long hedgers in terms of return, expected utility, risk adjusted returns and hedging cost. Additionally, the positive impact of estimated TVRA on systematic risk of the SET suggests that TVRA might be an alternative sentiment index of SET.